2011
DOI: 10.1257/aer.101.5.1872
|View full text |Cite
|
Sign up to set email alerts
|

Segregation and the Quality of Government in a Cross Section of Countries

Abstract: We provide a new compilation of data on ethnic, linguistic, and religious composition at the subnational level for a large number of countries. Using these data, we measure segregation of groups within the country. To overcome the endogeneity problem that arises because of mobility and endogenous internal borders, we construct an instrument for segregation. We find that more ethnically and linguistically segregated countries, i.e., those where groups live more spatially separately, have a lower quality of gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
286
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 448 publications
(317 citation statements)
references
References 39 publications
13
286
0
2
Order By: Relevance
“…The nonreligious were included in this measure because they also represent an important and often substantial subgroup in the religious composition of a country. Our measure correlated highly ( r = .81) with the well‐known religious fractionalization measure by Alesina and colleagues () and by Alesina and Zhuravskaya (). However, due to the limited coverage of European countries by the latter, this correlation was based on 18 countries only.…”
Section: Methodssupporting
confidence: 65%
“…The nonreligious were included in this measure because they also represent an important and often substantial subgroup in the religious composition of a country. Our measure correlated highly ( r = .81) with the well‐known religious fractionalization measure by Alesina and colleagues () and by Alesina and Zhuravskaya (). However, due to the limited coverage of European countries by the latter, this correlation was based on 18 countries only.…”
Section: Methodssupporting
confidence: 65%
“…In contrast, the ethnic inequality measure retains its statistical and economic significance. The coefficient on the ethnic Gini is unaffected when we condition on size and geography (in [4], [5], [8], and [9]).…”
Section: Ethnic Inequality and Developmentmentioning
confidence: 99%
“…14 In addition to social capital, the analysis also considers the degree of ethnic heterogeneity by including an ethnic fractionalization index, as in Gennaioli et al (2013). This is motivated by the fact that higher diversity is generally associated with lower levels of economic development (Alesina & Zhuravskaya, 2011;Beugelsdijk, Klasing & Milionis, 2017 the legacy of history on current TFP differences, we consider each region's historical urban density in 1800 based on data from Bairoch, Batou, and Chevre (1988). We also consider for each region how many cities were historically located on the crossing of two or more Roman roads, which Bosker et al (2013) have shown to be correlated with historical development over the past two millennia.…”
Section: Explanatory Variablesmentioning
confidence: 99%